2014
DOI: 10.1080/21642850.2014.889572
|View full text |Cite
|
Sign up to set email alerts
|

A quarter-century of HIV prevention intervention efforts among children and adolescents across the globe

Abstract: In 1988 a group of pediatricians, developmental, clinical, child and social psychologists, anthropologists and health educators began researching in Baltimore, Maryland on an HIV prevention intervention, Focus on Youth. Over the next 25 years the questions being addressed by Focus on Youth, reflected those of the global HIV research experience. During the first phase, the questions being addressed by the broader research community included: Can HIV risk behaviors be purposefully impacted by behavioral interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Very limited research evidence demonstrated that parents exposed to skills training in the Bahamas and Trinidad and Tobago reported a number of improvements: in their HIV knowledge and attitudes toward HIV/AIDS; in conversations with their children about sexuality, sexual risks, and protective factors; and in their monitoring of their children compared to parents in the control conditions. Parenting interventions, with high “doses” of intervention and booster sessions, seem to impact children’s self-reports of their enhanced HIV knowledge, their intentions to use a condom, higher condom use, and increased feelings of self-efficacy (PAHO, 2013; Stanton and Li, 2014). However, these few studies did not have sustained interventions with parents and their children across several developmental periods from pre-adolescence, through adolescence into young adulthood, which are deemed necessary to produce credible evidence of sustained behavioral changes in both groups.…”
Section: Micro-level Family Dynamics and Youth’s Sexual Attitudesmentioning
confidence: 99%
“…Very limited research evidence demonstrated that parents exposed to skills training in the Bahamas and Trinidad and Tobago reported a number of improvements: in their HIV knowledge and attitudes toward HIV/AIDS; in conversations with their children about sexuality, sexual risks, and protective factors; and in their monitoring of their children compared to parents in the control conditions. Parenting interventions, with high “doses” of intervention and booster sessions, seem to impact children’s self-reports of their enhanced HIV knowledge, their intentions to use a condom, higher condom use, and increased feelings of self-efficacy (PAHO, 2013; Stanton and Li, 2014). However, these few studies did not have sustained interventions with parents and their children across several developmental periods from pre-adolescence, through adolescence into young adulthood, which are deemed necessary to produce credible evidence of sustained behavioral changes in both groups.…”
Section: Micro-level Family Dynamics and Youth’s Sexual Attitudesmentioning
confidence: 99%
“…Beginning in 1990, with funding from NIH, the PMT-based FOK program was developed, implemented, and evaluated in Baltimore, MD, targeting urban African American adolescents (Stanton & Li, 2014). In 1998, the U.S. Center for Disease Control and Prevention (CDC) designated FOK as one of the Programs that Work nationwide in the U.S.…”
Section: Intervention Designmentioning
confidence: 99%
“…This study is continuing for more than 15 years funded by three separate National Institute of Health grant, and has yielded a rich data‐set resulting from multiple CRT implementations (eg, randomization is done at different levels in different NIH funded R01 based on progressive learning and implementation feasibility). The study has also resulted in multiple publications which can be found in Wang et al, 19 Li et al, 20 Stanton and Li, 21 Stanton et al, 22 and references therein. We carefully selected a section of the data that matches with the model () and assumptions made in the model.…”
Section: Application: Hiv Prevention Study In the Bahamasmentioning
confidence: 98%
“…Using the computed N 4 and the given parameters Δ, 𝛽 0 , 𝜏, 𝜌 1 = 0.5, 𝜌 2 = 0.1, and 𝜌 3 = 0.05 and 𝜉 as before we simulate Y and fit the linear mixed effect model using R "nlme" package. We follow the steps S1 to S11 as in Section 4 to compute the theoretical power ( 14) and the simulated power, only in S2 we use (21) to calculate N 4 . We present the level four sample size N 4 , theoretical power (𝜙), and simulated power ( φ) in Table 2 (additional results are in Tables 7 and 8 given in the supplementary materials), respectively for the three cost ratios.…”
Section: Simulation Studiesmentioning
confidence: 99%